Nanomechanical characterization of titanium incorporated gallium oxide nanocrystalline thin films. (June 2018) - Battu, A.K.; Manandhar, S.; Ramana, C.V.
Abstract: The effect of titanium (Ti) incorporation on the crystal structure and mechanical properties of nanocrystalline gallium oxide (Ga2 O3 ) films (Ga-Ti-O) is reported. Ti content was varied from 0 to ∼5 at% in the cosputter-deposited Ga-Ti-O films. The sputtering power applied to the Ti target was varied in the range of 0–100 W, while the sputtering power to Ga2 O3 was maintained at 100 W, to produce Ga-Ti-O films with variable Ti contents (0–5 at%). The Ti incorporation-induced effects were significant on the structural and mechanical properties. X-ray diffraction analysis indicated that structural transformation occurred with the increase in Ti content. The effect of Ti and associated microstructural changes are significant on the hardness (H) and elastic modulus (Er ). The H values increased continuously from 25 to 30 GPa as a function of Ti up to 1.5 at%, after which a decreasing trend was observed. The Ga-Ti-O films exhibited excellent mechanical characteristics: H ∼30 GPa, Er ∼310 GPa, H/Er ∼0.14, and H 3 / E r 2 ∼0.4 GPa, which are higher compared to those of intrinsic β-Ga2 O3 . On the basis of these results, a structure-composition-mechanical property correlation in Ga-Ti-O films is established. Graphical abstract: Highlights: Titanium incorporated Ga2 O3 nanocrystalline films were produced by sputter-deposition. The effect of Ti on the mechanical properties of Ga-Ti-O nano-films is reported. Titanium incorporation induces the structural transformations in Ga-Ti-O films. Microstructure changes as a function of Ti changes the harness and elastic modulus. Structure-composition-mechanical property relationship is established.